The Impact of Instagram as an Online Shop Media and Financial Literacy on Impulsive Buying Behavior among University Students - Dicky Iranto; Suparno Suparno; Fitri Rahmatun Nisa (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research is to ascertain how financial literacy and Instagram's role as an online retailer affect impulse purchases. The research method used is a survey. The population is students of the faculty of economics consist of 164 students as accessible population, and by using proportional random sampling, we choose 110 respondents. The data is linearly related and has a normally distributed distribution, according to the results of the requirements test. The classical assumption test has been passed by all variables. In the multicollinearity test, there is value tolerance from Instagram as an online shop media and financial literacy of 0.7090.01 and a VIF value of 1.41010. The regression equation obtained is Ỹ=14.588+0.808X1-0.110X2. Based on hypothesis test F test (Fcount Ftable), that is equal to 410.146 3.0811. Second, based on the Instagram t-test as an online shop media (tcount ttable), which is equal to 22.830 1.9823 and financial literacy of -2.102 1.9823. Based on the coefficient of determination, Instagram as an online shop media and financial literacy simultaneously affect 88% of impulsive buying behaviour. It concludes that Instagram and financial literacy has a positive and significant effect on student’s impulsive buying behavior.